Genetic improvement of banana using conventional and in vitro technologies. - Sipen, Philip; Chubo, John Keen; Hung, Patricia King Jie; Ong, Kian Huat; Davey, Michael R. (Taylor & Francis, 2011)

(untitled)
Banana (Musa spp.) is an important nutrient-rich fruit crop cultivated in the tropics and sub-tropics for local consumption and export. Targets for genetic improvement of banana range from improved fruit quality, yield, disease resistance, tolerance to biotic and abiotic stresses, and the biosynthesis of pharmaceutical compounds. Sterility has limited the success of generating new cultivars by conventional breeding. Tissue culture-based technologies that involve embryo rescue, the generation of somaclonal variation, and gene-transfer procedures are a useful adjunct to sexual hybridization, although considerable effort is required to establish robust protoplast-to-plant systems for somatic hybridization. Transformation involving Agrobacterium and biolistics- mediated gene transfer is feasible, underpinned by shoot regeneration from cultured cells and tissues. Molecular characterization of germplasm will facilitate the selection of material most relevant for incorporation into sexual and somatic genetic-improvement programs.